LEGAL GROUNDS FOR POLICE OFFICERS’ BODY-WORN CAMERAS - Milidragović, Dragan; Milic, Nenad; Petrovic, Zlatko (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Police organizations at the beginning of the 21st century are implementing body worn cameras (BWC). The use of BWC is based on specific legal provisions under which police officers record their actions and collect or process personal data. Based on the right to access to public information, the data collected in this way may become available to interested parties and pose a threat to the privacy of citizens. The Serbian police, following the trends in the modernization of world police forces, started a BWC implementation pilot project in September 2023, which should be followed up to a decision on their implementation in police practice. For this reason, legal provisions for the use of cameras in comparative legislation and ways to protect the privacy of citizens have been examined and analyzed in this paper. By analyzing comparative legislation and the Serbian Police Law, certain normative solutions regarding the use of BWC and the protection of citizens' privacy have been proposed.
Keywords: police officers; police organizations; cameras on police officers' uniforms; processing of personal data; privacy; privacy protection